Kajian Rantai Pasok Dan Pemasaran Daging Sapi Di Kabupaten Mempawah - Komariyati, Ismareni, Ani Muani, (Jurnal Social Economic of Agriculture, 2018)
Beef  is one of the food products that have no nutritional value in other to meet protein needs for the community. Beef supply chain is a concept that has a regulatory system relating to product flow, financial flow and information flow which jointly working to create and deliver a product into the hands of end users in the process of distribution of beef cattle live into beef. This study aims not only to determine the flow of products, financial flows and the flow of information in the beef supply chain, but also to analysis the efficiency of the level marketing. The study used description and analysc whith proportional random sampling and snowball sampling methods. The data is this study have been analysis by using marketing efficiency analysis, marketing margin, analysis and farmers share as well as profitability index. The results of this study as follow : (1) there streams in the beef supply chain in Mempawah Regency such as product flow, financial flows and information flow are not working well optimally; (2) the distribution channel of beef supply chain in Mempawah Regency is efficient based on efficiency of marketing value, marketing margins are profitable, the value of FS > MP and PI values that show the value of profits earned.Keywords : Supply Chain, Beef, Marketing